Performance in National Hockey League Players Decreases 1 Year After Undergoing Hip Arthroscopy With Return to Baseline by the Second Year - Emmitt Hayes, M.D.; Sasha Carsen, M.D., M.B.A.; Bogdan Matache, M.D.; Michael Pickell, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To evaluate performance following hip arthroscopy in National Hockey League (NHL) players. Methods: NHL players who underwent hip arthroscopy between 2008 and 2022 were identified through a publicly available injury database. Demographic and outcome data were collected for the 1-year period preceding and the 2-year period following surgery. Our primary outcome measure was wins above replacement per 60 minutes played (WAR/60), with secondary outcomes, including offensive and defensive goals, above replacement per 60 minutes played. A matched cohort was created on the basis of position, draft year, and index season performance. Preinjury and postinjury outcomes were compared using a paired t test. Results: Twenty-eight players underwent 29 eligible procedures. Preinjury, postinjury year 1, and postinjury year 2 WAR/60 were 0.06, 0.01, 0.04, respectively, in cases (P = .01, P = .12 compared to preinjury) and 0.07, 0.06, and 0.04, respectively, in controls (P = .35, P = .01, P = 0.82) compared to cases. Offensive goals above replacement per 60 minutes played were decreased compared to presurgery 1 and 2 years postsurgery but only performance 2 years postsurgery met statistical significance (P = .55, P = .03). Defensive goals above replacement per 60 minutes played were decreased compared to presurgery at postsurgery year 1 and 2, but only performance in year 1 was statistically significant (P = 0.01, P = .54). Postinjury defensive goals above replacement per 60 minutes played were significantly decreased compared to controls at postinjury year one (P = .03). Conclusions: NHL players who have undergone hip arthroscopy are associated with significantly decreased performance 1 year following surgery when compared with controls, driven primarily by decreased defensive performance. However, performance of major analytic metrics recovers by postinjury year 2. Level of Evidence: Level III, retrospective case-control study.